2021
DOI: 10.1038/s42003-021-02052-x
|View full text |Cite
|
Sign up to set email alerts
|

The highly dynamic nature of bacterial heteroresistance impairs its clinical detection

Abstract: Many bacterial species and antibiotic classes exhibit heteroresistance, a phenomenon in which a susceptible bacterial isolate harbors a resistant subpopulation that can grow in the presence of an antibiotic and cause treatment failure. The resistant phenotype is often unstable and without antibiotic selection it reverts back to susceptibility. Here we studied the dynamics by which these resistant subpopulations are enriched in the presence of antibiotic and recede back to their baseline frequency in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
0
27
1
Order By: Relevance
“…In China, the primary antibiotic resistance rates of H. pylori were 37.00% for CLA and 34.21% for LEV (Zhong et al, 2021). If heteroresistance cases are considered, the resistance rate for many antibiotics would be higher (Pereira et al, 2021;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In China, the primary antibiotic resistance rates of H. pylori were 37.00% for CLA and 34.21% for LEV (Zhong et al, 2021). If heteroresistance cases are considered, the resistance rate for many antibiotics would be higher (Pereira et al, 2021;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Due to phenotypic and genetic instability, heteroresistance is difficult to detect and study [ 16 , 18 , 19 ]. Rapid molecular and biochemical methods used to identify specific antibiotic resistance, such as real-time PCR or VITEK 2, are insufficient to detect heteroresistance due to the lack of a genetic marker or low sensitivity.…”
Section: Heteroresistance: Definition Detection Methods and Underlying Mechanismsmentioning
confidence: 99%
“…Heteroresistance may lead to antibiotic treatment failure due to the misclassification of heteroresistant isolates as susceptible strains. Consequently, inappropriate therapies fail to eradicate infections and facilitate the selection of resistant mutants [ 19 , 20 , 43 , 44 ]. It has been demonstrated that different antibiotics at levels below the MIC of the susceptible clinical isolates of E. coli and Salmonella enterica can cause the enrichment of resistant subpopulations with an increased copy number of resistance genes [ 19 ].…”
Section: Heteroresistance: Definition Detection Methods and Underlying Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity of an infecting bacterial population is an important consideration for the identification of an effective antibiotic treatment 1,2 . Some of the most common infectious diseases can be caused by more than one co-colonizing bacterial pathogen, incl.…”
Section: Introductionmentioning
confidence: 99%